1983
DOI: 10.1073/pnas.80.13.3948
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of proline-rich protein biosynthesis in rat parotid glands by sorghums with high tannin levels.

Abstract: Feeding of sorghum with a high level of tannin (high-tannin sorghum) to rats caused changes in gene expression in parotid glands similar to isoproterenol treatment. Within 3 days the parotid glands were enlarged about 3-fold and a series of proline-rich proteins were increased about 12-fold. Unlike isoproterenol treatment, no changes were observed in the submandibular glands, and a Mr 220,000 glycoprotein in parotid glands was not induced. Amino acid analyses, electrophoretic patterns, and cell-free translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
103
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(108 citation statements)
references
References 23 publications
4
103
0
1
Order By: Relevance
“…Here we show that the MSG1 protein also differs from classical proline-rich proteins in the regulation of its expression. Most proline-rich proteins in rodents are expressed at low basal levels in the SMGs and the parotids, and are induced by isoproterenol or tannin-rich diets Mehansho et al 1983Mehansho et al ,1987. Because of this induced expression and their capacity to bind polyphenols, such as tannins, it was proposed that these proline-rich proteins participate in dietary tannin detoxification.…”
Section: Discussionmentioning
confidence: 99%
“…Here we show that the MSG1 protein also differs from classical proline-rich proteins in the regulation of its expression. Most proline-rich proteins in rodents are expressed at low basal levels in the SMGs and the parotids, and are induced by isoproterenol or tannin-rich diets Mehansho et al 1983Mehansho et al ,1987. Because of this induced expression and their capacity to bind polyphenols, such as tannins, it was proposed that these proline-rich proteins participate in dietary tannin detoxification.…”
Section: Discussionmentioning
confidence: 99%
“…For example, feeding tannin-rich diets to rats and mice led to an initial weight loss. A normal weight gain resumed after about 3 days and was correlated with the induction of salivary PRP synthesis [6]. Hamsters are unable to induce salivary PRPs and also do not display the corresponding resumption of growth.…”
mentioning
confidence: 97%
“…Salivary PRps consist of between 70-80% proline, glutamine and glycine, arranged as 5-15 almost identical repeats of an approximate 18-residue sequence [4]. Their production is constitutive in man, but is at a very low level in some rodents, and can be induced either by isoprenaline [5] or by tannin-rich diets [6].…”
mentioning
confidence: 99%
“…There was evidence of hyperplasia and hypertrophy of the globlet cells (secretory mucus cells), and deaths occurring when chicks consumed the CT diets; however, no deaths occurred in the rats (Ortiz et al 1994). Mehansho et al (1983) demonstrated that rats fed a high tannin sorghum diet developed parotid glands that were enlarged threefold within 3 d of feeding the diet, and a series of proline-rich proteins (PRP) capable of binding CT increased 12-fold. Likely, the ability of the rats to adapt to the high CT diet by increasing the secretion of proline-rich proteins reduced the negative impacts compared to the chicks consuming the same high tannin diets.…”
Section: Mots Clésmentioning
confidence: 99%